The simpler, the better: Measuring financial conditions for monetary policy and financial stability - Simone Arrigoni; Alina Bobasu; Fabrizio Venditti (European Investment Bank (EIB), 2021)
In this paper we assess the merits of financial condition indices constructed using simple averages versus a more sophisticated alternative that uses factor models with time varying parameters. Our analysis is based on data for 18 advanced and emerging economies at a monthly frequency covering about 70% of the world's GDP.We assess the performance of these indicators based on their ability to capture tail risk for economic activity and to predict banking and currency crises. We find that averaging across the indicators of interest, using judgmental but intuitive weights, produces financial condition indices that are not inferior to, and actually perform better than, those constructed with more sophisticated statistical methods. An indicator that gives more weight to measures of financial stress, which we term WA-FSI, emerges as the best indicator for anticipating banking crisis, and is therefore better suited for financial stability.
Keywords: E32; E44; C11; C55; 330; financial conditions; quantile regressions; banking crises; SVARs; spillovers